2000
DOI: 10.1016/s0035-9203(00)90317-1
|View full text |Cite
|
Sign up to set email alerts
|

RFLP patterns and risk factors for recent tuberculosis transmission among hospitalized tuberculosis patients in Rio de Janeiro, Brazil

Abstract: Isolates of Mycobacterium tuberculosis from 120 tuberculosis patients seen in the 12 months ending September 1994 at 2 tertiary-care centres in Rio de Janeiro were characterized by IS6110 restriction fragment length polymorphism (RFLP) analysis. Ninety-seven patients (81%) had isolates with unique RFLP patterns, while 23 patients (19%) had isolates that belonged to 11 different RFLP cluster patterns. The strains from the latter patients were distributed among 1 group of 3 patients and 10 groups of 2 patients e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
5
13
1
Order By: Relevance
“…These results agree partially with those published by other Brazilian authors [7,27]. In our study, HIV infection was not associated with isolate clustering, although 48.3% of the patients were HIV positive.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results agree partially with those published by other Brazilian authors [7,27]. In our study, HIV infection was not associated with isolate clustering, although 48.3% of the patients were HIV positive.…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with previous works [7,27,32] utilizing the detection of insertion element IS6110 in Brazilian M. tuberculosis isolates, which demonstrated that the number of this element per genome may vary (2-12 copies per genome). Our results also demonstrate that most of the isolates may be allocated to two main clusters.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In a retrospective study carried out to evaluate indicators of TB risk transmission, where 63.5% of patients were admitted to the hospital through the Emergency Room, in 27.5% of them the interval between admission and sputum collection exceeded 12 h. This delay in isolation was correlated with diagnosis of TB at admission and lower bacillary load in the sputum (16). In previous Brazilian MDR case studies, there was a significant association with clustering, suggesting that at tertiary care hospitals MDR cases may result from new transmission of primary resistant organisms (17). According to this information, a patient could be infected with one genetic pattern of MDR strain transmitted through the health facilities where he was admitted and the variant pattern found was related to an event of microevolution through IS6110 transposition over time.…”
Section: Patient Follow-up Results and Discussionmentioning
confidence: 80%